2021
DOI: 10.1177/03795721211019638
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Underweight, Overweight, and Obesity: A Cross-Sectional Study of Sociodemographic, Dietary, and Lifestyle Factors Among Adolescent Girls in Jutiapa, Guatemala

Abstract: Background: As the incidence of overweight continues to increase among children and adolescents in Guatemala, underweight remains a prominent health problem. However, the prevalence of overweight or underweight and associated risk factors has not been investigated among adolescent girls. Objective: To determine the prevalence of underweight and overweight/obesity and associated sociodemographic, dietary, and lifestyle factors among adolescent girls in Jutiapa, Guatemala. Methods: A cross-sectional study of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Larger family size meant more children, a more dispersed distribution of food, and a greater likelihood of being thinner compared to devoting all resources to one individual. Some studies have found only a child to be a risk factor for obesity, somewhat similar to the present study ( 31 , 46 , 47 ). The prevalence of thinness was found to be higher in boys only when the paternal age at childbirth was older than 30 years old.…”
Section: Discussionsupporting
confidence: 90%
“…Larger family size meant more children, a more dispersed distribution of food, and a greater likelihood of being thinner compared to devoting all resources to one individual. Some studies have found only a child to be a risk factor for obesity, somewhat similar to the present study ( 31 , 46 , 47 ). The prevalence of thinness was found to be higher in boys only when the paternal age at childbirth was older than 30 years old.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, obese students are also more likely to be bullied because of poor body size and athleticism [33] . Our research found that high blood pressure increased the risk of overweight and obesity, yet many studies show that overweight and obesity are independently associated with incident hypertension in a Chinese population [34][35][36] . Currently, the effect of hypertension on overweight and obesity is not very clear, and the mechanism of the interaction between them needs to be further explored.…”
Section: Discussionmentioning
confidence: 83%